Influência do período de maturação e das estações do ano nos parâmetros físico-químicos e microbiológicos do queijo Minas artesanal da região do Serro - Valeria Macedo Cardoso (2011)
Minas traditional Serro cheese is a product that has a high consumption and appreciation in Brazil. The main objective of this work was to verify the ripening and dry and rainy seasons influence on hygienical-sanitary indicators, pathogenic microorganisms, Staphylococcal enterotoxins and physicochemical characteristics of this cheese to find out the microbiological and physicochemical quality of this product. In addition, yeast populations, volatile compound composition and amine biogenic contents were also determined. This study was made with cheeses produced by five farmers that were in the last part of good manufacturing practices implement and have certification by the Instituto Mineiro de Agropecuária. Fifty samples produced in dry season and 50 produced in the rainy season were collected. Ten cheeses with two days of ripening were collected from each farm that was stored in a cold room, without package, until complete the desired ripening period. Analyses were made with two cheeses from each farmer with 3, 15, 30, 45 and 60 days of ripening. High levels of total and fecal coliforms and E. coli were found in the beginning of ripening period decreasing with 60 days. The contamination by coagulasepositive Staphylococci was reduced at the end of the ripening period. After 45 days of ripening the cheeses made in dry and in the rainy seasons presented coagulase-positive Staphylococci counts under the limit recommended by the Brazilian legislation (1000 cfu/g). Salmonella spp. was not detected. SEC and TSST-1 were detected in three and five samples, respectively from cheeses manufactured on dry season. From the cheeses of the rainy season analyzed, one presented simultaneously SEB, SEC and TSST-1 and 16 samples presented TSST-1. None of the 9 pools from isolates of Staphylococcus spp. analyzed produced the enterotoxins A, B, C and D, although three pools produced TSST-1. The great variation on percentages of moisture, fat content in the dry matter and protein indicate the lack of standardization of the cheesemaking process of the traditional Serro Minas cheese. Seventeen yeast species were identified during the ripening, being Debaryomyces hansenii, Kodamaea ohmeri and Kluyveromyces marxianus the most prevalent species. An increase in the yeast counts was found during cheese ripening. Some species were detected only in the cheese manufactured in the dry season and others were detected only in the cheese manufactured in the rainy season. Biogenic amines such as putrescine, cadaverine, spermidine, 2- phenylethylamine, spermine and tryptamine had high contents during ripening, in the cheese manufactured in the dry season; histamine, in the cheese manufactured in both seasons and agmatine, in the cheese manufactured in the rainy season. Tryptamine and histamine showed higher contents in the cheese manufactured in the dry and rainy seasons, respectively. Individually, biogenic amines searched not reached contents that could cause adverse effects to human health. A total of 53 volatile compounds were detected during the cheese and 50 were identified in the cheese manufactured in the rainy season, being detected aromatic compounds, fatty acids, hydrocarbons, alcohols, esters, ketones and terpenes. Some volatile compounds disappeared during ripening and others come out. Other compounds were detected in the cheese in all ripening period. The high pathogen and coliform levels in the beginning of ripening for the cheese produced in both seasons indicates the need for an improvement of the hygienic sanitary conditions of the milk used in the production of this cheese. The great variation on physicochemical parameters indicates the lack of standardization of the cheesemaking process of the cheese. The yeast, biogenic amines and volatile compounds determination contributed to characterize the traditional Serro cheese